Temporary foreign workers with lower-skill occupations in the food manufacturing industry: Transition to permanent residency and industrial retention after transition - Jue Zhang; Yuqian Lu; Youjin Choi; Jianwei Zhong (Economic and Social Reports, 2024)
The COVID-19 pandemic has put a spotlight on the roles played by temporary foreign workers with lower-skill occupations in the food manufacturing sector, and concerns have been raised about whether they have sufficient pathways to become permanent residents and whether they stay in the sector after obtaining their permanent residency. This study focuses on these workers and examines their transition to permanent residency and their industrial retention after immigration.